Urea Application to Enhance Sugarcane Trash Decomposition: A Field Test in PTPN VII of Cinta Manis District in South Sumatera - Putri, Kenny Marlian; Setyawan, Dwi; Priatna, Satria Jaya (Universitas Sebelas Maret, 2020)
Sugarcane harvest results in plant residues, consisting of leaves, stems and roots nearly 20 ton ha-1. The plantation of PTPN VII in Cinta Manis District applied urea with a dosage of 5 kg ha-1 but the result was not effective. There is a potential to try a higher dosage of urea to enhance trash decomposition. This research aims to evaluate urea application on biomass decomposition. This research was conducted on the Plot 07 Rayon 3 of PTPN VII, District of Cinta Manis at Ketiau, Lubuk Keliat of Ogan Ilir, South Sumatra, using Split Plot design. Main plot is trash sampling time and subplot is urea dosage with three replicates. ANCOVA was used for soil data. The rate of decomposition of the litter was calculated by the change in the initial condition of research with each week on observation resulting in decomposition rate graphs. Urea application at 10 kg ha-1 reduced C/N of the litter ratio to almost 21:1 and was followed by the highest total nitrogen increase to 0.18%, while the highest organic carbon decline for urea treatment of 6 kg ha-1 amounted to 13.78%. In conclusion, higher rate of urea application is still required to enhance sugarcane litter decomposition.